Degradable mask cloth and preparation method thereof

By grafting furan and maleimide groups in the mask cloth material, combining silk protein gel and modified cellulose nanocrystals, a reversible covalent bond network is formed, and the active ingredients are encapsulated in microcapsules, the problems of non-degradable, poor mechanical properties and low utilization of active ingredients are solved, and a high-performance, fully degraded and intelligent mask cloth material is achieved.

CN119837768AActive Publication Date: 2025-04-18SHANGHAI MEANLOVE BIO-TECH CO LTD

Patent Information

Application Number
CN202510336601.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

The existing mask fabric materials are non-degradable, resulting in environmental pollution, poor mechanical properties and low utilization rate of active ingredients.

Method used

By grafting furan and maleimide groups in the molecular chain of polyethylene glycol-polylactic acid, crosslinking polymers are formed and combined with silk protein gel and modified cellulose nanocrystals, a reversible covalent bond network is formed by photocrosslinking and hot pressing. Meanwhile, sea grape polyphenols and collagen peptides were encapsulated in the inner layer of liposomes and were encapsulated in chitosan-polyN-isopropylacrylamide microcapsules, and loaded into the mask cloth by vacuum impregnation.

Benefits of technology

The degradability of the mask cloth is realized, its mechanical properties and utilization rate of active ingredients are improved, and the requirements of degradation cycle, tensile strength, active ingredient release rate, self-healing efficiency, binding force, biocompatibility and storage stability are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119837768A_ABST
    Figure CN119837768A_ABST
Patent Text Reader

Abstract

The invention provides degradable mask cloth and a preparation method thereof, and belongs to the field of mask base materials. The method comprises the following steps: grafting a furan group and a maleimide group in a molecular chain of polyethylene glycol-polylactic acid to obtain a cross-linked polymer; injecting a cross-linked polymer solution into the fibroin gel, adding a photoinitiator and the modified cellulose nanocrystal dispersion liquid, and then performing ultraviolet irradiation to obtain a composite film; carrying out hot pressing on the composite film to obtain a base material; the preparation method comprises the following steps: encapsulating sea grape polyphenol and collagen peptide in an inner layer of a liposome, and then encapsulating in a chitosan-poly (N-isopropylacrylamide) microcapsule to obtain a microcapsule compound with a core-shell structure; grafting sulfydryl on the surface of the microcapsule compound, and then loading the microcapsule compound in a base material to obtain the mask cloth. Through innovative design of a dynamic covalent bond network, natural-synthetic hybridization enhancement, intelligent double-response microcapsules and an environment-friendly process, a high-performance, full-degradable and intelligent mask cloth material is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of facial mask basic materials, and in particular to a degradable facial mask cloth and a preparation method thereof. Background Art

[0002] Facial mask cloth is a carrier material used in skin care products. It is mainly used to carry essence and fit the skin, delivering active ingredients (such as moisturizers, antioxidants, peptides, etc.) to the skin surface through physical transfer and sustained release.

[0003] Most of the facial mask cloths currently on the market are made of non-degradable synthetic polymer materials, which form microplastic pollution after being discarded, and the degradation cycle exceeds 100 years, which seriously damages the ecological environment. Although the existing technology attempts to replace it with bio-based materials such as polylactic acid or chitosan, there are still significant defects: polylactic acid is highly brittle and easy to tear when wet, while chitosan is degradable but has weak mechanical properties and quickly softens and fails after absorbing moisture. At the same time, the active ingredients in the facial mask cloth are easily oxidized and inactivated during ultraviolet or high-temperature processing, resulting in low utilization of the active ingredients in the facial mask cloth. Therefore, how to improve the mechanical properties of the facial mask cloth and the utilization rate of the active ingredients in the facial mask cloth on the basis of improving the degradability of the facial mask cloth is a technical problem that urgently needs to be solved. Summary of the invention

[0004] The present application provides a degradable facial mask cloth and a preparation method thereof to solve the following technical problem: how to improve the mechanical properties of the facial mask cloth and the utilization rate of the active ingredients in the facial mask cloth on the basis of improving the degradability of the facial mask cloth.

[0005] In a first aspect, the present application provides a method for preparing a degradable facial mask cloth, the method comprising: Grafting furan groups and maleimide groups into the molecular chain of polyethylene glycol-polylactic acid to obtain a cross-linked polymer; the grafting rate of the furan groups is ≥15%, and the grafting rate of the maleimide groups is ≥10%; The cross-linked polymer solution is injected into the silk protein gel, and a photoinitiator and a modified cellulose nanocrystal dispersion are added, and then ultraviolet light is irradiated to initiate a photocrosslinking reaction to obtain a composite film; the photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphonate, and its mass is 0.5-1% of the total mass of the composite film; the modified cellulose nanocrystal is amino-modified cellulose nanocrystal, and its mass is 1-2% of the total mass of the composite film; hot pressing the composite film to form a reversible covalent bond network to obtain a substrate; Sea grape polyphenols and collagen peptides are encapsulated in the inner layer of liposomes, and then encapsulated in chitosan-poly N-isopropylacrylamide microcapsules to obtain a core-shell structure microcapsule complex; the particle size of the liposome is 100-150 nm, the particle size of the microcapsule complex is 500-800 nm, and the mass ratio of the chitosan to the poly N-isopropylacrylamide is 3:(6-8); The surface of the microcapsule composite is grafted with a thiol group, and then loaded into the substrate by a vacuum impregnation method to obtain a facial mask cloth.

[0006] Optionally, the step of grafting furan groups and maleimide groups into the molecular chain of polyethylene glycol-polylactic acid to obtain a cross-linked polymer comprises: The hydroxy-activated polyethylene glycol-polylactic acid, furan methanol, stannous octoate and dichloromethane are mixed to cause a grafting reaction of the furan group to obtain a furan grafted polymer; Under a nitrogen atmosphere, the furan grafted polymer, maleimide-polyethylene glycol-succinimide ester, triethylamine and dichloromethane are mixed to cause a grafting reaction of the maleimide group, and then a purification treatment is performed to obtain the cross-linked polymer.

[0007] Optionally, the mass ratio of the hydroxyl-activated polyethylene glycol-polylactic acid, the furan carbinol and the stannous octoate is 100:(20-30):(0.5-1.5); The mass ratio of the furan grafted polymer, the maleimide-polyethylene glycol-succinimide ester and the triethylamine is 100:(30-40):(2-4); The heating temperature of the grafting reaction of the furan group is 75 to 85° C., and the reaction time is 24 to 48 hours; The temperature of the grafting reaction of the maleimide group is room temperature, and the reaction time is 6 to 18 hours.

[0008] Optionally, the particle size of the modified cellulose nanocrystals is 100 to 200 nm; The ultraviolet light irradiation includes the following parameters: the ultraviolet light wavelength is 405 nm, the irradiation intensity is 5-10 mW / cm², and the irradiation time is 10-15 min; The hot pressing includes the following parameters: temperature 60-70° C., pressure 0.5-1 MPa, and time 10-15 min.

[0009] Optionally, the preparation method of the silk protein gel comprises: Glutamine transaminase is added to the silk protein solution to carry out a cross-linking reaction, and then the solution is allowed to stand to form a gel to obtain a silk protein gel; the mass concentration of the silk protein in the silk protein solution is 6-8%, and the mass of the glutamine transaminase is 1-3 U / g of the silk protein mass.

[0010] Optionally, the sea grape polyphenols and collagen peptides are encapsulated in the inner layer of liposomes, and then encapsulated in chitosan-poly N-isopropylacrylamide microcapsules to obtain a core-shell structure microcapsule complex, comprising: Soybean lecithin, cholesterol and α-tocopherol were dissolved in chloroform and then rotary evaporated to form a membrane to obtain a lipid membrane; dissolving sea grape polyphenols and collagen peptides in phosphate buffer to obtain a hydration solution; adding the hydration liquid to the lipid film, and then performing ultrasonic treatment to obtain a liposome suspension; The poly (N-isopropylacrylamide) microgel and the chitosan solution are mixed, and then the liposome suspension is added and homogenized to obtain a suspension; A sodium tripolyphosphate solution is added dropwise to the suspension to perform ionic cross-linking, followed by centrifugation to obtain the microcapsule complex.

[0011] Optionally, the mass ratio of the soybean lecithin, the cholesterol and the α-tocopherol is (75-85):(15-25):(0.5-1); The concentration of the phosphate buffer is 0.01 M and the pH is 6.8-7.2; The concentration of the sea grape polyphenol is 1 to 5 mg / mL, and the concentration of the collagen peptide is 5 to 10 mg / mL; The mass concentration of chitosan in the chitosan solution is 1-3%, and the solvent is 1% acetic acid solution; The particle size of the poly (N-isopropylacrylamide) microgel is 100 to 200 nm; The mass ratio of chitosan in the chitosan solution to the poly (N-isopropylacrylamide) microgel is 3:(6-8); The dropping rate of the sodium tripolyphosphate solution is 1-2 mL / min, and the final concentration of the sodium tripolyphosphate in the suspension is 0.1-0.3%.

[0012] Optionally, the rotary evaporation includes the following parameters: temperature of 35 to 40°C, vacuum degree of -0.08 to -0.1 MPa, rotation speed of 80 to 100 rpm, and time of 30 to 60 min; The homogenization process includes the following parameters: a rotation speed of 10,000 to 15,000 rpm, a time of 5 to 10 minutes, and a cycle number of 2 to 3 times; The centrifugation includes the following parameters: centrifugal force of 5000-8000×g, time of 10-15 min, and temperature of 4-10°C.

[0013] Optionally, the step of grafting thiol groups on the surface of the microcapsule composite and then loading the microcapsule composite into the substrate by vacuum impregnation to obtain a facial mask cloth comprises: The microcapsule complex is immersed in an ethanol solution containing 3-mercaptopropyltrimethoxysilane, and the pH is adjusted to 4.0-5.0 to cause a thiol grafting reaction to obtain a thiol-modified microcapsule complex; the reaction temperature of the thiol grafting reaction is 50-60° C., and the reaction time is 4-6 hours; The thiol-modified microcapsule complex is loaded into the substrate by a vacuum impregnation method to obtain a facial mask cloth.

[0014] In a second aspect, the present application provides a facial mask cloth obtained by the preparation method of the degradable facial mask cloth described in any one of the first aspects, wherein the facial mask cloth satisfies the following properties: The degradation period is 4 to 6 months; The dry tensile strength is 20-22MPa; The wet tensile strength is 10-12MPa; Under the conditions of pH 5.5 and 32-37℃, the cumulative release rate of sea grape polyphenols was ≥80% and the cumulative release rate of collagen peptides was ≥85% within 24 hours. Repair at 60℃ for 5min, self-repair efficiency ≥95; The bonding force is 8-10N / cm; Biocompatibility ≥95%; Storage stability ≥90%.

[0015] The above technical solution provided by this application has the following advantages compared with the prior art: The present application provides a method for preparing a degradable mask cloth. First, polyethylene glycol-polylactic acid and silk protein substrates and microcapsules are all degradable materials. At the same time, furan and maleimide groups form dynamic covalent bonds through reversible Diels-Alder reactions, and the mask material can be rapidly degraded in the natural environment; secondly, the dynamic bonds formed by furan and maleimide groups can be preferentially broken and consumed when subjected to force, and microcracks can be repaired by thermally triggered recombination, significantly improving tear resistance. In addition, amino cellulose nanocrystals are combined with polymer matrix through hydrogen bonds and mechanical interlocking effects to improve dry tensile strength; finally, a core-shell structure microcapsule complex is loaded in the mask, chitosan can be dissolved in the weakly acidic environment of the skin, and the active ingredients are released. The poly N-isopropylacrylamide microgel shrinks and squeezes the inner core at body temperature, accurately triggering the release of the active ingredients. At the same time, the thiol grafted on the surface of the microcapsule is covalently bonded to the maleimide group of the substrate, which improves the binding force between the microcapsule and the mask substrate. Thereby, on the basis of improving the degradability of the mask cloth, the mechanical properties of the mask cloth and the utilization rate of the active ingredients in the mask cloth are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings herein are incorporated in and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the description, are used to explain the principles of the present application.

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0018] Figure 1 A schematic flow chart of a method for preparing a degradable facial mask cloth provided in an embodiment of the present application. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0020] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0021] Figure 1A schematic flow chart of a method for preparing a degradable facial mask cloth provided in an embodiment of the present application.

[0022] First, as Figure 1 As shown, the present application provides a method for preparing a degradable facial mask cloth, the method comprising: S1. Grafting furan groups and maleimide groups into the molecular chain of polyethylene glycol-polylactic acid to obtain a cross-linked polymer; the grafting rate of the furan groups is ≥15%, and the grafting rate of the maleimide groups is ≥10%; In some embodiments, the grafting of furan groups and maleimide groups into the molecular chain of polyethylene glycol-polylactic acid to obtain a cross-linked polymer comprises: The hydroxy-activated polyethylene glycol-polylactic acid, furan methanol, stannous octoate and dichloromethane are mixed to cause a grafting reaction of the furan group to obtain a furan grafted polymer; Under a nitrogen atmosphere, the furan grafted polymer, maleimide-polyethylene glycol-succinimide ester, triethylamine and dichloromethane are mixed to cause a grafting reaction of the maleimide group, and then a purification treatment is performed to obtain the cross-linked polymer.

[0023] In some embodiments, the mass ratio of the hydroxyl-activated polyethylene glycol-polylactic acid, the furan carbinol and the stannous octoate is 100:(20-30):(0.5-1.5); The mass ratio of the furan grafted polymer, the maleimide-polyethylene glycol-succinimide ester and the triethylamine is 100:(30-40):(2-4); The heating temperature of the grafting reaction of the furan group is 75 to 85° C., and the reaction time is 24 to 48 hours; The temperature of the grafting reaction of the maleimide group is room temperature, and the reaction time is 6 to 18 hours.

[0024] It should be noted that the synthesis of the dynamically cross-linked polymer in S1 has the following effects: (1) Introduction of dynamic covalent bonds: The furan group and the maleimide group form reversible covalent bonds through the Diels-Alder reaction, giving the material self-healing ability.

[0025] (2) Furan grafting rate ≥ 15% and maleimide grafting rate ≥ 10%: This can ensure that the dynamic bond density is high enough to achieve efficient self-repairing (repair rate ≥ 90% at 60°C).

[0026] (3) Enhanced material stability: The cross-linked polymer backbone (PEG-PLA) provides mechanical support, and the dynamic bond network allows thermally triggered recombination after local damage, thereby extending the service life.

[0027] (4) Environmentally friendly and degradable: PEG-PLA is a biodegradable material. Its hydrolysis products are lactic acid and polyethylene glycol. It can be completely degraded in the soil within 4 to 6 months, thus avoiding microplastic pollution.

[0028] S2, injecting the cross-linked polymer solution into the silk protein gel, adding a photoinitiator and a modified cellulose nanocrystal dispersion, and then irradiating with ultraviolet light to initiate a photocrosslinking reaction to obtain a composite film; the photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphonate, and its mass is 0.5-1% of the total mass of the composite film; the modified cellulose nanocrystal is amino-modified cellulose nanocrystal, and its mass is 1-2% of the total mass of the composite film; In some embodiments, the particle size of the modified cellulose nanocrystals is 100-200 nm, and the mass is 1-2% of the total mass of the composite film.

[0029] In some embodiments, the ultraviolet light irradiation includes the following parameters: the ultraviolet light wavelength is 405 nm, the irradiation intensity is 5 to 10 mW / cm², and the irradiation time is 10 to 15 min.

[0030] In some embodiments, the method for preparing the silk protein gel comprises: Glutamine transaminase is added to the silk protein solution to carry out a cross-linking reaction, and then the solution is allowed to stand to form a gel to obtain a silk protein gel; the mass concentration of the silk protein in the silk protein solution is 6-8%, and the mass of the glutamine transaminase is 1-3 U / g of the silk protein mass.

[0031] It should be noted that the photo-crosslinking and nanocrystal enhancement of the composite film in S2 have the following effects: (1) Construction of interpenetrating network: Silk protein gel can provide natural hydrophilicity and biocompatibility, enhance the flexibility and skin adhesion of the material. The photoinitiator (LAP) can generate active free radicals under 405 nm ultraviolet light, triggering the cross-linking of PEG-PLA and silk protein to form a stable three-dimensional network.

[0032] (2) Strengthening of mechanical properties: Amino modification of modified cellulose nanocrystals can enhance the interfacial bonding with polymers and reduce agglomeration. The particle size is 100-200 nm, and the addition amount is 1-2%. It can improve the dry strength and wet tear resistance of the composite film through hydrogen bonding and mechanical interlocking.

[0033] (3) Optimization of UV light parameters: Controlling the wavelength of UV light to 405 nm can avoid the damage of short-wave UV light to the active ingredients while ensuring the efficiency of photoinitiation. Controlling the irradiation intensity to 5-10 mW / cm² and the irradiation time to 10-15 min can balance the cross-linking depth and material damage and prevent embrittlement caused by excessive cross-linking.

[0034] S3, hot pressing the composite film to form a reversible covalent bond network to obtain a substrate; In some embodiments, the hot pressing includes the following parameters: temperature 60-70° C., pressure 0.5-1 MPa, and time 10-15 min.

[0035] It should be noted that the reversible covalent bond network formed by hot pressing in S3 has the following effects: (1) Dynamic bond network activation: The hot pressing temperature is controlled at 60-70°C, close to the glass transition temperature of PLA, to soften the material segments and promote the dynamic bond reorganization of furan and maleimide. The hot pressing pressure is controlled at 0.5-1 MPa to evenly distribute the dynamic bonds, avoid local stress concentration, and form a uniform cross-linked network.

[0036] (2) Improve material toughness: Dynamic bonds break and dissipate energy first when subjected to stress, preventing crack propagation and maintaining high strength even in wet state.

[0037] S4, encapsulating sea grape polyphenols and collagen peptides in the inner layer of liposomes, and then encapsulating them in chitosan-poly N-isopropylacrylamide microcapsules to obtain a core-shell structure microcapsule complex; the particle size of the liposome is 100-150 nm, the particle size of the microcapsule complex is 500-800 nm, and the mass ratio of the chitosan to the poly N-isopropylacrylamide is 3:(6-8); In some embodiments, the sea grape polyphenols and collagen peptides are encapsulated in the inner layer of liposomes, and then encapsulated in chitosan-poly N-isopropylacrylamide microcapsules to obtain a core-shell structure microcapsule complex, comprising: S401, dissolving soybean lecithin, cholesterol and α-tocopherol in chloroform, and then rotary evaporating to form a film to obtain a lipid film; S402, dissolving sea grape polyphenols and collagen peptides in phosphate buffer to obtain a hydration solution; S403, adding the hydration liquid to the lipid membrane, and then performing ultrasonic treatment to obtain a liposome suspension; S404, mixing the poly (N-isopropylacrylamide) microgel with the chitosan solution, adding the liposome suspension, and homogenizing to obtain a suspension; S405, adding sodium tripolyphosphate solution dropwise to the suspension to perform ionic crosslinking, and then centrifuging to obtain the microcapsule complex.

[0038] In some embodiments, the mass ratio of the soybean lecithin, the cholesterol and the α-tocopherol is (75-85):(15-25):(0.5-1); The concentration of the phosphate buffer is 0.01 M and the pH is 6.8-7.2; The concentration of the sea grape polyphenol is 1 to 5 mg / mL, and the concentration of the collagen peptide is 5 to 10 mg / mL; The mass concentration of chitosan in the chitosan solution is 1-3%, and the solvent is 1% acetic acid solution; The particle size of the poly (N-isopropylacrylamide) microgel is 100 to 200 nm; The mass ratio of chitosan in the chitosan solution to the poly (N-isopropylacrylamide) microgel is 3:(6-8); The dropping rate of the sodium tripolyphosphate solution is 1-2 mL / min, and the final concentration of the sodium tripolyphosphate in the suspension is 0.1-0.3%.

[0039] In some embodiments, the rotary evaporation comprises the following parameters: temperature of 35 to 40° C., vacuum degree of -0.08 to -0.1 MPa, rotation speed of 80 to 100 rpm, and time of 30 to 60 min; The homogenization process includes the following parameters: a rotation speed of 10,000 to 15,000 rpm, a time of 5 to 10 minutes, and a cycle number of 2 to 3 times; The centrifugation includes the following parameters: centrifugal force of 5000-8000×g, time of 10-15 min, and temperature of 4-10°C.

[0040] It should be noted that the preparation of the core-shell microcapsule composite in S4 has the following effects: (1) Active ingredient protection and controlled release: The inner layer of the liposome is controlled to be 100-150 nm, so that the soybean phospholipid / cholesterol membrane protects sea grape polyphenols (photothermosensitive) and collagen peptides (easily hydrolyzed), and the encapsulation rate is ≥85%. α-Tocopherol acts as an antioxidant to extend the shelf life of the active ingredients. The thickness of the chitosan-PNIPAM shell is controlled to be 500-800 nm, chitosan: PNIPAM = 3: (6-8), chitosan can provide pH response (dissolved at pH 5.5), PNIPAM can provide temperature response (contracted at 32°C), and dual-trigger release can be achieved. The microcapsule structure can be stabilized by ionic crosslinking to avoid sudden release.

[0041] (2) Stability and targeting: Homogenization can ensure that the liposomes are evenly dispersed, and centrifugation can be used to remove unencapsulated components to improve drug loading efficiency.

[0042] S5, grafting thiol groups on the surface of the microcapsule composite, and then loading it into the substrate by vacuum impregnation method to obtain a facial mask cloth.

[0043] In some embodiments, the method of grafting thiol groups on the surface of the microcapsule composite and then loading the microcapsule composite into the substrate by vacuum impregnation to obtain a facial mask cloth comprises: The microcapsule complex is immersed in an ethanol solution containing 3-mercaptopropyltrimethoxysilane, and the pH is adjusted to 4.0-5.0 to cause a thiol grafting reaction to obtain a thiol-modified microcapsule complex; the reaction temperature of the thiol grafting reaction is 50-60° C., and the reaction time is 4-6 hours; The thiol-modified microcapsule complex is loaded into the substrate by a vacuum impregnation method to obtain a facial mask cloth.

[0044] It should be noted that the thiol grafting and vacuum impregnation loading in S5 have the following effects: (1) Surface functionalization enhances binding strength: Thiol grafting can covalently bind to the maleimide group in the substrate through a click reaction, thereby improving the binding strength of the microcapsule complex. Vacuum impregnation can drive the microcapsules to penetrate into the pores of the substrate under negative pressure.

[0045] (2) Uniform distribution and long-term stability: After vacuum release, the pressure difference causes the microcapsules to be tightly embedded in the matrix. Freeze-drying or low-temperature drying retains the active ingredients, and the storage stability is ≥12 months.

[0046] In a second aspect, the present application provides a facial mask cloth obtained by the preparation method of the degradable facial mask cloth described in any one of the first aspects, wherein the facial mask cloth satisfies the following properties: The degradation period is 4 to 6 months; The dry tensile strength is 20-22MPa; The wet tensile strength is 10-12MPa; Under the conditions of pH 5.5 and 32-37℃, the cumulative release rate of sea grape polyphenols was ≥80% and the cumulative release rate of collagen peptides was ≥85% within 24 hours. Repair at 60℃ for 5min, self-repair efficiency ≥95; The bonding force is 8-10N / cm; Biocompatibility ≥95%; Storage stability ≥90%.

[0047] In summary, the biodegradable facial mask cloth and preparation method thereof provided in this application have the following advantages: 1. Dynamic covalent bond network and self-healing performance (1) Double-group synergistic dynamic crosslinking: Furan-maleimide Diels-Alder reaction: PEG-PLA polymer grafted with furan and maleimide double groups is introduced into the biodegradable facial mask cloth to form a reversible covalent bond network, achieving a microcrack repair rate of ≥90% at 60°C.

[0048] (2) High grafting rate and controllable degradation: Through the optimization of hydroxyl activation and esterification reaction process, the balance between dynamic bond density and degradation rate is ensured (complete degradation in 4 to 6 months). At the same time, the degradation products are lactic acid and polyethylene glycol, with no microplastic residue, which is far superior to traditional polyacrylate mask materials.

[0049] 2. Natural-Synthetic Hybrid Structures (1) Silk protein and PEG-PLA interpenetrating network (IPN): The natural β-folding structure of silk protein is used to improve the flexibility of the composite film (dry tensile strength ≥15 MPa, wet tensile strength ≥8 MPa), overcoming the brittleness of pure PLA materials.

[0050] (2) Innovation in photocross-linking process: Using 405 nm visible light initiator (LAP) instead of traditional ultraviolet light (254 nm) to reduce damage to active ingredients while ensuring uniform cross-linking depth.

[0051] (3) Nanocrystal reinforcement and interface optimization: Aminated cellulose nanocrystals (CNC) strengthen the PLA / silk protein interface through hydrogen bonding and mechanical interlocking, thereby improving wet tear resistance.

[0052] 3. Core-shell microcapsule intelligent release system (1) Dual-response controlled release mechanism: Chitosan (dissolved at pH 5.5) can match the weakly acidic environment on the skin surface and release sea grape polyphenols (antioxidant). PNIPAM (contracted at 32°C) triggers the release of collagen peptides at body temperature, with a cumulative release rate of ≥85% over 24 hours.

[0053] (2) Optimization of structural parameters: The liposome core protects sensitive components, and the microcapsule shell ensures sustained-release stability, thereby achieving an encapsulation rate ≥ 85%.

[0054] 4. Interface bonding process (1) Thiol-maleimide click chemistry: Thiol groups are introduced onto the surface of microcapsules through MPTMS treatment and covalently bonded to the substrate maleimide.

[0055] (2) Fully degradable material system: The substrate (PEG-PLA) and microcapsules (chitosan-PNIPAM) are both biodegradable materials with a degradation cycle of 4 to 6 months, which complies with the requirements of EU REACH and China's "Plastic Ban".

[0056] It can be seen that this application systematically solves the core problems of traditional facial mask cloths such as non-degradability, poor wet mechanical properties, low utilization of active ingredients and process toxicity residues through the innovative design of dynamic covalent bond networks, natural-synthetic hybrid enhancement, intelligent dual-responsive microcapsules and environmentally friendly processes, and provides a high-performance, fully degradable and intelligent next-generation skin care material solution.

[0057] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0058] Example 1 This embodiment provides a method for preparing a degradable facial mask cloth, the method comprising the following steps: S11, mixing hydroxy-activated polyethylene glycol-polylactic acid (source: Ruixi Biotechnology, purity 95%), furan methanol, stannous octoate and dichloromethane to cause a grafting reaction of the furan group to obtain a furan grafted polymer; then, under a nitrogen atmosphere, mixing the furan grafted polymer, maleimide-polyethylene glycol-succinimide ester (product model: McLean, M864396), triethylamine and dichloromethane to cause a grafting reaction of the maleimide group, and then purifying to obtain the cross-linked polymer; Wherein, the grafting rate of the furan group is 15%, and the grafting rate of the maleimide group is 10%; The mass ratio of the hydroxyl-activated polyethylene glycol-polylactic acid, the furan carbinol and the stannous octoate is 100:25:1; The mass ratio of the furan graft polymer, the maleimide-polyethylene glycol-succinimide ester and the triethylamine is 100:35:3; The heating temperature of the furan group grafting reaction is 80°C and the reaction time is 36h; The temperature of the grafting reaction of the maleimide group is room temperature, and the reaction time is 12 hours; S21, adding glutamine aminotransferase (CAS No. 80146-85-6, enzyme activity 120) to a silk protein solution (product model SFS-1) to carry out a cross-linking reaction, and then standing to form a gel to obtain a silk protein gel; then injecting the cross-linked polymer solution into the silk protein gel, and adding a photoinitiator and a modified cellulose nanocrystal dispersion, and then irradiating with ultraviolet light to induce a photocross-linking reaction to obtain a composite film; The mass concentration of silk protein in the silk protein solution is 7%, and the mass of the glutamine aminotransferase is 2 U / g of silk protein; The photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphonate, and its mass is 0.8% of the total mass of the composite film; The modified cellulose nanocrystals are amino-modified cellulose nanocrystals with a particle size of 100 to 150 nm and a mass of 1.5% of the total mass of the composite film; The preparation method of the amino-modified cellulose nanocrystals is as follows: a cellulose nanocrystal suspension is mixed with EDC and NHS in a mass ratio of 1:0.2:0.1, the pH is adjusted to 5.0, stirred at room temperature for 2 hours, and then ethylenediamine (with a mass ratio of 1:1 to the cellulose nanocrystals) is added, the pH is adjusted to 9.0, reacted in a water bath at 60° C. for 6 hours, and purified and dried to obtain the amino-modified cellulose nanocrystals; The ultraviolet light irradiation includes the following parameters: the ultraviolet light wavelength is 405 nm, the irradiation intensity is 8 mW / cm², and the irradiation time is 12 min; S31, hot pressing the composite film to form a reversible covalent bond network to obtain a substrate; The hot pressing process includes the following parameters: temperature 65°C, pressure 0.7MPa, time 12min; S41, dissolving soybean lecithin (CAS No.: 8002-43-5), cholesterol (CAS No.: 57-88-5) and α-tocopherol (CAS No.: 59-02-9) in chloroform, and then rotary evaporating to form a film to obtain a lipid film; dissolving sea grape polyphenol (CAS No. 84929-27-1) and collagen peptide (CAS No. 2239-67-0) in phosphate buffer to obtain a hydration solution; adding the hydration solution to the lipid film, and then ultrasonically treating to obtain a liquid suspension; mixing poly N-isopropylacrylamide microgel (product model PNIPAM-40,000) with chitosan (CAS No. 9012-76-4) solution, and then adding liposome suspension, and homogenizing to obtain a suspension. Adding sodium tripolyphosphate solution to the suspension to perform ionic crosslinking, and then centrifuging to obtain the microcapsule complex; Wherein, the particle size of the liposome is 100-120 nm, the particle size of the microcapsule complex is 500-600 nm, and the mass ratio of the chitosan to the poly N-isopropylacrylamide is 3:7; The mass ratio of the soybean lecithin, the cholesterol and the α-tocopherol is 80:20:0.7; The concentration of the phosphate buffer is 0.01 M and the pH is 7.0; The concentration of the sea grape polyphenol is 3 mg / mL, and the concentration of the collagen peptide is 8 mg / mL; The mass concentration of chitosan in the chitosan solution is 2%, and the solvent is 1% acetic acid solution; The particle size of the poly (N-isopropylacrylamide) microgel is 100 to 150 nm; The mass ratio of chitosan in the chitosan solution to the poly (N-isopropylacrylamide) microgel is 3:7; The sodium tripolyphosphate solution has a dropwise acceleration rate of 1 to 2 mL / min, and the final concentration of the sodium tripolyphosphate in the suspension is 0.2%; The rotary evaporation includes the following parameters: temperature of 35 to 40°C, vacuum degree of -0.08 to -0.1 MPa, speed of 90 rpm, and time of 40 min; The homogenization process includes the following parameters: rotation speed is 12000 rpm, time is 8 min, and number of cycles is 3 times; The centrifugation parameters include: centrifugal force of 6000×g, time of 12 min, and temperature of 7°C.

[0059] S51, immersing the microcapsule complex in an ethanol solution containing 3-mercaptopropyltrimethoxysilane (CAS No. 4420-74-0), adjusting the pH to 4.0-5.0 to allow a thiol grafting reaction to occur, thereby obtaining a thiol-containing microcapsule complex; using a vacuum impregnation method, loading the thiol-containing microcapsule complex into the substrate, thereby obtaining a facial mask cloth.

[0060] The reaction temperature of the thiol grafting reaction is 55° C. and the reaction time is 5 h.

[0061] Example 2 This embodiment provides a method for preparing a degradable facial mask cloth, the method comprising the following steps: S11, mixing hydroxy-activated polyethylene glycol-polylactic acid (source: Ruixi Biotechnology, purity 95%), furan methanol, stannous octoate and dichloromethane to cause a grafting reaction of the furan group to obtain a furan grafted polymer; then, under a nitrogen atmosphere, mixing the furan grafted polymer, maleimide-polyethylene glycol-succinimide ester (product model: McLean, M864396), triethylamine and dichloromethane to cause a grafting reaction of the maleimide group, and then purifying to obtain the cross-linked polymer; Wherein, the grafting rate of the furan group is 16%, and the grafting rate of the maleimide group is 12%; The mass ratio of the hydroxyl-activated polyethylene glycol-polylactic acid, the furan alcohol and the stannous octoate is 100:20:0.5; The mass ratio of the furan graft polymer, the maleimide-polyethylene glycol-succinimide ester and the triethylamine is 100:30:2; The heating temperature of the furan group grafting reaction is 75°C and the reaction time is 48h; The temperature of the grafting reaction of the maleimide group is room temperature, and the reaction time is 6 hours; S21, adding glutamine aminotransferase (CAS No. 80146-85-6, enzyme activity 120) to a silk protein solution (product model SFS-1) to carry out a cross-linking reaction, and then standing to form a gel to obtain a silk protein gel; then injecting the cross-linked polymer solution into the silk protein gel, and adding a photoinitiator and a modified cellulose nanocrystal dispersion, and then irradiating with ultraviolet light to induce a photocross-linking reaction to obtain a composite film; The mass concentration of silk protein in the silk protein solution is 6%, and the mass of the glutamine transaminase is 1 U / g of silk protein. The photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphonate, and its mass is 0.5% of the total mass of the composite film; The modified cellulose nanocrystals are amino-modified cellulose nanocrystals with a particle size of 100 to 150 nm and a mass of 1% of the total mass of the composite film; The preparation method of the amino-modified cellulose nanocrystals is as follows: a cellulose nanocrystal suspension is mixed with EDC and NHS in a mass ratio of 1:0.2:0.1, the pH is adjusted to 5.0, stirred at room temperature for 2 hours, and then ethylenediamine (with a mass ratio of 1:1 to the cellulose nanocrystals) is added, the pH is adjusted to 9.0, reacted in a water bath at 60° C. for 6 hours, and purified and dried to obtain the amino-modified cellulose nanocrystals; The ultraviolet light irradiation includes the following parameters: the ultraviolet light wavelength is 405 nm, the irradiation intensity is 5 mW / cm², and the irradiation time is 15 min; S31, hot pressing the composite film to form a reversible covalent bond network to obtain a substrate; The hot pressing process includes the following parameters: temperature 60°C, pressure 0.5MPa, time 15min; S41, dissolving soybean lecithin (CAS No.: 8002-43-5), cholesterol (CAS No.: 57-88-5) and α-tocopherol (CAS No.: 59-02-9) in chloroform, and then rotary evaporating to form a film to obtain a lipid film; dissolving sea grape polyphenol (CAS No.: 84929-27-1) and collagen peptide (CAS No.: 2239-67-0) in phosphate buffer to obtain a hydration solution; adding the hydration solution to the lipid film, and then ultrasonically treating to obtain a liquid suspension; mixing poly N-isopropylacrylamide microgel (product model: PNIPAM-40,000) with chitosan (CAS No.: 9012-76-4) solution, and then adding liposome suspension, and homogenizing to obtain a suspension; dropping sodium tripolyphosphate solution into the suspension to perform ionic crosslinking, and then centrifuging to obtain the microcapsule complex; Wherein, the particle size of the liposome is 100-120 nm, the particle size of the microcapsule complex is 600-800 nm, and the mass ratio of the chitosan to the poly (N-isopropylacrylamide) is 3:6; The mass ratio of the soybean lecithin, the cholesterol and the α-tocopherol is 75:15:0.5; The concentration of the phosphate buffer is 0.01 M and the pH is 7; The concentration of the sea grape polyphenol is 1 mg / mL, and the concentration of the collagen peptide is 5 mg / mL; The mass concentration of chitosan in the chitosan solution is 1%, and the solvent is 1% acetic acid solution; The particle size of the poly (N-isopropylacrylamide) microgel is 100 to 120 nm; The mass ratio of chitosan in the chitosan solution to the poly (N-isopropylacrylamide) microgel is 3:6; The dropping rate of the sodium tripolyphosphate solution is 1 mL / min, and the final concentration of the sodium tripolyphosphate in the suspension is 0.1%; The rotary evaporation includes the following parameters: temperature of 35°C, vacuum degree of -0.08 to -0.1 MPa, rotation speed of 80 rpm, and time of 60 min; The homogenization process includes the following parameters: rotation speed is 10000 rpm, time is 5 min, and number of cycles is 3 times; The centrifugation parameters include: centrifugal force of 5000×g, time of 15 min, and temperature of 4°C.

[0062] S51, immersing the microcapsule complex in an ethanol solution containing 3-mercaptopropyltrimethoxysilane (CAS No. 4420-74-0), adjusting the pH to 4.0-5.0 to allow a thiol grafting reaction to occur, thereby obtaining a thiol-containing microcapsule complex; using a vacuum impregnation method, loading the thiol-containing microcapsule complex into the substrate, thereby obtaining a facial mask cloth.

[0063] The reaction temperature of the thiol grafting reaction is 50° C. and the reaction time is 6 hours.

[0064] Example 3 This embodiment provides a method for preparing a degradable facial mask cloth, the method comprising the following steps: S11, mixing hydroxy-activated polyethylene glycol-polylactic acid (source: Ruixi Biotechnology, purity 95%), furan methanol, stannous octoate and dichloromethane to cause a grafting reaction of the furan group to obtain a furan grafted polymer; then, under a nitrogen atmosphere, mixing the furan grafted polymer, maleimide-polyethylene glycol-succinimide ester (product model: McLean, M864396), triethylamine and dichloromethane to cause a grafting reaction of the maleimide group, and then purifying to obtain the cross-linked polymer; Wherein, the grafting rate of the furan group is 15%, and the grafting rate of the maleimide group is 10%; The mass ratio of the hydroxyl-activated polyethylene glycol-polylactic acid, the furan carbinol and the stannous octoate is 100:30:1.5; The mass ratio of the furan graft polymer, the maleimide-polyethylene glycol-succinimide ester and the triethylamine is 100:40:4; The heating temperature of the grafting reaction of the furan group is 85°C and the reaction time is 24h; The temperature of the grafting reaction of the maleimide group is room temperature, and the reaction time is 18 hours; S21, adding glutamine aminotransferase (CAS No. 80146-85-6, enzyme activity 120) to a silk protein solution (product model SFS-1) to carry out a cross-linking reaction, and then standing to form a gel to obtain a silk protein gel; then injecting the cross-linked polymer solution into the silk protein gel, and adding a photoinitiator and a modified cellulose nanocrystal dispersion, and then irradiating with ultraviolet light to induce a photocross-linking reaction to obtain a composite film; The mass concentration of silk protein in the silk protein solution is 8%, and the mass of the glutamine aminotransferase is 3 U / g of silk protein. The photoinitiator is phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium, and its mass is 1% of the total mass of the composite film; The modified cellulose nanocrystals are amino-modified cellulose nanocrystals with a particle size of 150 to 200 nm and a mass of 2% of the total mass of the composite film; The preparation method of the amino-modified cellulose nanocrystals is as follows: a cellulose nanocrystal suspension is mixed with EDC and NHS in a mass ratio of 1:0.2:0.1, the pH is adjusted to 5.0, stirred at room temperature for 2 hours, and then ethylenediamine (with a mass ratio of 1:1 to the cellulose nanocrystals) is added, the pH is adjusted to 9.0, reacted in a water bath at 60° C. for 6 hours, and purified and dried to obtain the amino-modified cellulose nanocrystals; The ultraviolet light irradiation includes the following parameters: the ultraviolet light wavelength is 405 nm, the irradiation intensity is 10 mW / cm², and the irradiation time is 10 min; S31, hot pressing the composite film to form a reversible covalent bond network to obtain a substrate; The hot pressing process includes the following parameters: temperature 70°C, pressure 1 MPa, time 10 min; S41, dissolving soybean lecithin (CAS No.: 8002-43-5), cholesterol (CAS No.: 57-88-5) and α-tocopherol (CAS No.: 59-02-9) in chloroform, and then rotary evaporating to form a film to obtain a lipid film; dissolving sea grape polyphenol (CAS No.: 84929-27-1) and collagen peptide (CAS No.: 2239-67-0) in phosphate buffer to obtain a hydration solution; adding the hydration solution to the lipid film, and then ultrasonically treating to obtain a liquid suspension; mixing poly N-isopropylacrylamide microgel (product model: PNIPAM-40,000) with chitosan (CAS No.: 9012-76-4) solution, and then adding liposome suspension, and homogenizing to obtain a suspension; dropping sodium tripolyphosphate solution into the suspension to perform ionic crosslinking, and then centrifuging to obtain the microcapsule complex; Wherein, the particle size of the liposome is 120-150 nm, the particle size of the microcapsule complex is 600-700 nm, and the mass ratio of the chitosan to the poly (N-isopropylacrylamide) is 3:8; The mass ratio of the soybean lecithin, the cholesterol and the α-tocopherol is 85:25:1; The concentration of the phosphate buffer is 0.01 M and the pH is 7; The concentration of the sea grape polyphenol is 5 mg / mL, and the concentration of the collagen peptide is 10 mg / mL; The mass concentration of chitosan in the chitosan solution is 3%, and the solvent is 1% acetic acid solution; The particle size of the poly (N-isopropylacrylamide) microgel is 150 to 200 nm; The mass ratio of chitosan in the chitosan solution to the poly (N-isopropylacrylamide) microgel is 3:8; The dropping rate of the sodium tripolyphosphate solution is 2 mL / min, and the final concentration of the sodium tripolyphosphate in the suspension is 0.3%; The rotary evaporation includes the following parameters: temperature of 40°C, vacuum degree of -0.08 to -0.1 MPa, rotation speed of 100 rpm, and time of 30 min; The homogenization process includes the following parameters: rotation speed is 15000 rpm, time is 5 min, and number of cycles is 2 times; The centrifugation parameters include: centrifugal force of 8000×g, time of 10 min, and temperature of 4°C.

[0065] S51, immersing the microcapsule complex in an ethanol solution containing 3-mercaptopropyltrimethoxysilane (CAS No. 4420-74-0), adjusting the pH to 4.0-5.0 to allow a thiol grafting reaction to occur, thereby obtaining a thiol-containing microcapsule complex; using a vacuum impregnation method, loading the thiol-containing microcapsule complex into the substrate, thereby obtaining a facial mask cloth.

[0066] The reaction temperature of the thiol grafting reaction is 60° C. and the reaction time is 4 hours.

[0067] Comparative Example 1 This comparative example is modified as follows based on the disclosure of Example 1: In step S11, only furan groups are grafted into the molecular chains of the hydroxyl-activated polyethylene glycol-polylactic acid.

[0068] Comparative Example 2 This comparative example is modified as follows based on the disclosure of Example 1: In step S11, only maleimide groups are grafted into the molecular chains of the hydroxyl-activated polyethylene glycol-polylactic acid.

[0069] Comparative Example 3 This comparative example is modified as follows based on the disclosure of Example 1: In step S11, no furan group and no maleimide group are grafted into the molecular chain of the hydroxyl-activated polyethylene glycol-polylactic acid.

[0070] Comparative Example 4 In step S21, no modified cellulose nanocrystal dispersion is added.

[0071] Comparative Example 5 This comparative example is modified as follows based on the disclosure of Example 1: In step S41, sea grape polyphenols and collagen peptides are not encapsulated in liposomes and microcapsules.

[0072] Comparative Example 6 This comparative example is modified as follows based on the disclosure of Example 1: In step S41, the sea grape polyphenols and collagen peptides are directly encapsulated in chitosan-poly (N-isopropylacrylamide) microcapsules without being coated with liposomes.

[0073] Comparative Example 7 This comparative example is modified as follows based on the disclosure of Example 1: In step S51, the surface thiol groups of the microcapsule complex are not grafted, and the microcapsule complex is directly loaded into the substrate to obtain a facial mask cloth.

[0074] The properties of the facial mask fabrics of Examples 1 to 3 and Comparative Examples 1 to 7 were measured, and the results are shown in Table 1. The performance measurement method is as follows: Degradation cycle: Soil burial test (ISO 20200), measuring the time for the sample weight loss rate to be ≥ 90%.

[0075] Dry / wet tensile strength: Universal materials testing machine (ASTM D638), tensile rate 5 mm / min, wet samples are tested after immersion for 24 hours.

[0076] Release rate of active ingredients: In vitro dissolution test (USP 42), pH 5.5 phosphate buffer, 32°C constant temperature water bath, HPLC (sea grape polyphenols) and BCA method (collagen peptides) to determine the cumulative release amount.

[0077] Self-repair efficiency: SEM observation of the morphology of microcracks (width ≤ 50 μm) before and after repair, tensile strength recovery rate = (strength after repair / original strength) × 100%.

[0078] Adhesion (peel strength): 90° peel test (ASTM D1876), testing the peel strength of the interface between substrate and microcapsules.

[0079] Biocompatibility: Human fibroblasts (HaCaT) were cultured for 48 hours and the survival rate was determined by CCK-8 method (ISO 10993-5).

[0080] Storage stability: 40℃ / 75% humidity accelerated test for 3 months, HPLC / BCA method for determining active ingredient retention rate.

[0081] Table 1 Performance of the facial mask cloths of Examples 1 to 3 and Comparative Examples 1 to 7

[0082] As shown in Table 1, Examples 1 to 3 are significantly superior to the comparative examples in terms of degradability, mechanical properties, and active utilization rate through dual dynamic bond networks, nanocrystal reinforcement, and core-shell microcapsule design. The degradation period of the mask cloths of Examples 1 to 3 is 4 to 6 months, the dry tensile strength is 20 to 22 MPa, the wet tensile strength is 10 to 12 MPa, and the cumulative release rate of sea grape polyphenols within 24 hours is ≥80% and the cumulative release rate of collagen peptides is ≥85% under pH 5.5 and 32 to 37°C. The self-repair efficiency is ≥95 after repairing at 60°C for 5 minutes, the binding force is 8 to 10 N / cm, the biocompatibility is ≥95%, and the storage stability is ≥90%.

[0083] Comparative Example 1 only grafts furan groups and lacks maleimide groups, so it is unable to form a dynamic covalent bond network and has low self-repair efficiency.

[0084] In Comparative Example 2, only maleimide groups were grafted, resulting in insufficient dynamic bond density, low self-repair efficiency, and decreased activity release due to weak microcapsule binding force.

[0085] Comparative Example 3 has no dynamic group grafted, the material is highly brittle and has no self-repairing ability, and the active ingredients are rapidly degraded due to the lack of microcapsule protection.

[0086] In Comparative Example 4, no modified cellulose nanocrystals (CNC) were added, the interface bonding force was weak, and the wet tensile strength decreased.

[0087] Comparative Example 5 was not coated with liposomes, the active ingredient was directly exposed, the burst release rate was high, and the storage stability was poor.

[0088] Comparative Example 6 did not coat the liposome core, the collagen peptide was prone to leakage, and the stability decreased.

[0089] Comparative Example 7 has no grafted thiol group, and the microcapsules are only physically adsorbed to the substrate, with low binding force and are easy to fall off during use.

[0090] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0091] In addition, in the description of the specification of this application, the terms "include", "comprises", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0092] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a degradable facial mask cloth, characterized in that: The method comprises: Grafting furan groups and maleimide groups into the molecular chain of polyethylene glycol-polylactic acid to obtain a cross-linked polymer; the grafting rate of the furan groups is ≥15%, and the grafting rate of the maleimide groups is ≥10%; The cross-linked polymer solution is injected into the silk protein gel, and a photoinitiator and a modified cellulose nanocrystal dispersion are added, and then ultraviolet light is irradiated to initiate a photocrosslinking reaction to obtain a composite film; the photoinitiator is phenyl-2,4,6-trimethylbenzoyl lithium phosphonate, and its mass is 0.5-1% of the total mass of the composite film; the modified cellulose nanocrystal is amino-modified cellulose nanocrystal, and its mass is 1-2% of the total mass of the composite film; hot pressing the composite film to form a reversible covalent bond network to obtain a substrate; Sea grape polyphenols and collagen peptides are encapsulated in the inner layer of liposomes, and then encapsulated in chitosan-poly N-isopropylacrylamide microcapsules to obtain a core-shell structure microcapsule complex; the particle size of the liposome is 100-150 nm, the particle size of the microcapsule complex is 500-800 nm, and the mass ratio of the chitosan to the poly N-isopropylacrylamide is 3:(6-8); The surface of the microcapsule composite is grafted with a thiol group, and then loaded into the substrate by a vacuum impregnation method to obtain a facial mask cloth.

2. The method for preparing the degradable facial mask cloth according to claim 1, characterized in that: The method of grafting furan groups and maleimide groups into the molecular chain of polyethylene glycol-polylactic acid to obtain a cross-linked polymer comprises: The hydroxy-activated polyethylene glycol-polylactic acid, furan methanol, stannous octoate and dichloromethane are mixed to cause a grafting reaction of the furan group to obtain a furan grafted polymer; Under a nitrogen atmosphere, the furan grafted polymer, maleimide-polyethylene glycol-succinimide ester, triethylamine and dichloromethane are mixed to cause a grafting reaction of the maleimide group, and then a purification treatment is performed to obtain the cross-linked polymer.

3. The method for preparing the degradable facial mask cloth according to claim 2, characterized in that: The mass ratio of the hydroxy-activated polyethylene glycol-polylactic acid, the furan carbinol and the stannous octoate is 100:(20-30):(0.5-1.5); The mass ratio of the furan grafted polymer, the maleimide-polyethylene glycol-succinimide ester and the triethylamine is 100:(30-40):(2-4); The heating temperature of the grafting reaction of the furan group is 75 to 85° C., and the reaction time is 24 to 48 hours; The temperature of the grafting reaction of the maleimide group is room temperature, and the reaction time is 6 to 18 hours.

4. The method for preparing the degradable facial mask cloth according to claim 1, characterized in that: The particle size of the modified cellulose nanocrystal is 100 to 200 nm; The ultraviolet light irradiation includes the following parameters: the ultraviolet light wavelength is 405 nm, the irradiation intensity is 5-10 mW / cm², and the irradiation time is 10-15 min; The hot pressing includes the following parameters: temperature 60-70° C., pressure 0.5-1 MPa, and time 10-15 min.

5. The method for preparing the degradable facial mask cloth according to claim 1, characterized in that: The preparation method of the silk protein gel comprises: Glutamine transaminase is added to the silk protein solution to carry out a cross-linking reaction, and then the solution is allowed to stand to form a gel to obtain a silk protein gel; the mass concentration of the silk protein in the silk protein solution is 6-8%, and the mass of the glutamine transaminase is 1-3 U / g of the silk protein mass.

6. The method for preparing the degradable facial mask cloth according to claim 1, characterized in that: The method encapsulates sea grape polyphenols and collagen peptides in the inner layer of liposomes, and then encapsulates them in chitosan-poly N-isopropylacrylamide microcapsules to obtain a core-shell structure microcapsule complex, comprising: Soybean lecithin, cholesterol and α-tocopherol were dissolved in chloroform and then rotary evaporated to form a membrane to obtain a lipid membrane; dissolving sea grape polyphenols and collagen peptides in phosphate buffer to obtain a hydration solution; adding the hydration liquid to the lipid film, and then performing ultrasonic treatment to obtain a liposome suspension; The poly (N-isopropylacrylamide) microgel and the chitosan solution are mixed, and then the liposome suspension is added and homogenized to obtain a suspension; A sodium tripolyphosphate solution is added dropwise to the suspension to perform ionic cross-linking, followed by centrifugation to obtain the microcapsule complex.

7. The method for preparing the degradable facial mask cloth according to claim 6, characterized in that: The mass ratio of the soybean lecithin, the cholesterol and the α-tocopherol is (75-85):(15-25):(0.5-1); The concentration of the phosphate buffer is 0.01 M and the pH is 6.8-7.2; The concentration of the sea grape polyphenol is 1 to 5 mg / mL, and the concentration of the collagen peptide is 5 to 10 mg / mL; The mass concentration of chitosan in the chitosan solution is 1-3%, and the solvent is 1% acetic acid solution; The particle size of the poly (N-isopropylacrylamide) microgel is 100 to 200 nm; The mass ratio of chitosan in the chitosan solution to the poly (N-isopropylacrylamide) microgel is 3:(6-8); The dropping rate of the sodium tripolyphosphate solution is 1-2 mL / min, and the final concentration of the sodium tripolyphosphate in the suspension is 0.1-0.3%.

8. The method for preparing the degradable facial mask cloth according to claim 6, characterized in that: The rotary evaporation includes the following parameters: temperature of 35 to 40°C, vacuum degree of -0.08 to -0.1 MPa, rotation speed of 80 to 100 rpm, and time of 30 to 60 min; The homogenization process includes the following parameters: a rotation speed of 10,000 to 15,000 rpm, a time of 5 to 10 minutes, and a cycle number of 2 to 3 times; The centrifugation includes the following parameters: centrifugal force of 5000-8000×g, time of 10-15 min, and temperature of 4-10° C.

9. The method for preparing the degradable facial mask cloth according to claim 1, characterized in that: The method of grafting thiol groups on the surface of the microcapsule composite and then loading them into the substrate by vacuum impregnation to obtain a facial mask cloth comprises: The microcapsule complex is immersed in an ethanol solution containing 3-mercaptopropyltrimethoxysilane, and the pH is adjusted to 4.0-5.0 to cause a thiol grafting reaction to obtain a thiol-modified microcapsule complex; the reaction temperature of the thiol grafting reaction is 50-60° C., and the reaction time is 4-6 hours; The thiol-modified microcapsule complex is loaded into the substrate by a vacuum impregnation method to obtain a facial mask cloth.

10. A facial mask cloth obtained by the preparation method of the degradable facial mask cloth according to any one of claims 1 to 9, characterized in that: The facial mask fabric meets the following properties: The degradation period is 4 to 6 months; The dry tensile strength is 20-22MPa; The wet tensile strength is 10-12MPa; Under the conditions of pH 5.5 and 32-37℃, the cumulative release rate of sea grape polyphenols was ≥80% and the cumulative release rate of collagen peptides was ≥85% within 24 hours. Repair at 60℃ for 5min, self-repair efficiency ≥95; The bonding force is 8-10N / cm; Biocompatibility ≥95%; Storage stability ≥90%.

Citation Information

Patent Citations

  • Copolymer of fibroin and poly D,L-lactic acid, preparation method and application thereof

    CN101445607A

  • Corn polylactic acid short-fiber spunlaced face mask material

    CN101491486A

  • Polylactic acid nanometer complex concurrently having toughness and strength, and preparation method thereof

    CN105295324A

  • Small molecule peptide mask fabric and production method thereof

    CN108078856A

  • Porous PVA / cellulose nanocrystalline hydrogel and preparation method thereof

    CN110498993A

Cited By

  • Temperature-sensitive color-changing degradable material and bionic artware thereof

    CN121450115A